2010
DOI: 10.1055/s-0029-1245144
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Sonographic Screening of the Flow in the Basilar Artery during Head Rotation Reduces the Risk for Sudden Infant Death

Abstract: Hypoperfusion of the brain stem may be a significant risk factor of SIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The reason for development of brain stem hypoperfusion, resulting in desaturation or bradycardia, could not be determined in our study. Several studies have suggested that position‐dependent hypoperfusion of the brain stem caused by abnormal blood flow of the basilar‐vertebral system may be a risk factor for sudden infant death 8 , 9 . In our study, diastolic blood flow in the basilar and vertebral arteries and systolic blood flow in the vertebral arteries were lower in premature than term neonates.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The reason for development of brain stem hypoperfusion, resulting in desaturation or bradycardia, could not be determined in our study. Several studies have suggested that position‐dependent hypoperfusion of the brain stem caused by abnormal blood flow of the basilar‐vertebral system may be a risk factor for sudden infant death 8 , 9 . In our study, diastolic blood flow in the basilar and vertebral arteries and systolic blood flow in the vertebral arteries were lower in premature than term neonates.…”
Section: Discussionsupporting
confidence: 47%
“…Low blood flow and volume in the blood supply of the brain stem may cause malfunction of the brain stem, leading to central apnea or sudden infant death 5 , 6 . Prospective sonographic studies of healthy neonates examined position‐dependent blood flow in the basilar artery to evaluate hypoperfusion of the brain stem as a risk factor for sudden infant death 7 , 8 . A further study with 3259 neonates defined standard velocity values in the vertebral arteries of healthy term neonates 9 .…”
mentioning
confidence: 99%
“…The cervical position-induced changes in the blood flow of vertebral arteries are associated with the disturbances in the blood supply of the brainstem, and several studies have assessed its role in SIDS 9,10) . Based on their results, the authors suggest avoidance of risky rotated positions either supine or prone 11) , emphasising that the lateral position is urgently recommended as the sleeping position in infants 12) . This is because in some infants, the rotated head positions during sleep (especially rotation in prone) can cause position-dependent circulatory disturbance in the vertebrobasilar circuit.…”
Section: Resultsmentioning
confidence: 99%
“…The aim is to investigate positional hypoperfusion of the brain stem, which is considered a risk factor for sudden infant death. 1 The neonate was the second child of a 30-year old white woman. Pregnancy and birth were uneventful.…”
mentioning
confidence: 99%